TATA KELOLA PENGARSIPAN DI BAGIAN HUKUM SEKRETARIAT DAERAH PEMERINTAH KOTA TANGERANG SELATAN (Lembaga Pengembangan Kinerja Dosen, 2022)
The development of information technology today is increasingly demanding the need for information for every organization or agency. One of the main sources that can help us in supporting the process of administrative activities is archives. The purpose of making this research article is to find out the management of archive management in the legal section of the regional secretariat of the South Tangerang city government which includes the mechanism of outgoing and incoming letters and the factors for creating efficient archive management according to Sugiarto and Wahyono (2015). The method used is a qualitative research method. The results in this research article are by looking at the criteria above, it can be concluded that the management of archives in the legal section of the regional secretariat of the South Tangerang city government can be said to be good. however, new innovations such as electronic-based archiving are needed.